2018
DOI: 10.1177/1758835918804151
|View full text |Cite
|
Sign up to set email alerts
|

Durvalumab in NSCLC: latest evidence and clinical potential

Abstract: Advances in immunotherapy have led to radical improvements in outcomes, including overall survival, such as in non-small cell lung cancer (NSCLC) patients with metastatic disease treated with immune checkpoint inhibitors. More recently, promising results have been obtained in earlier disease settings, and combinations with other therapies are being actively investigated. Durvalumab, a monoclonal antibody directed against the programmed death ligand 1, has demonstrated significant activity in NSCLC, including i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
28
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 24 publications
(28 citation statements)
references
References 73 publications
0
28
0
Order By: Relevance
“…For instance, anti-PD1 and anti-PD-L1 drugs prevent PD-L1 (and PD-L2) from interacting with PD-1, which would normally allow a decrease in T-cells function signaling and their activation against cells. 51 …”
Section: Action Mechanisms: Dissimilarities Among Anti- Pd1 and Anti-mentioning
confidence: 99%
See 2 more Smart Citations
“…For instance, anti-PD1 and anti-PD-L1 drugs prevent PD-L1 (and PD-L2) from interacting with PD-1, which would normally allow a decrease in T-cells function signaling and their activation against cells. 51 …”
Section: Action Mechanisms: Dissimilarities Among Anti- Pd1 and Anti-mentioning
confidence: 99%
“…On one hand, this results in a possible higher efficacy even in low PD-L1 tumors, but this would potentially generate more severe irAEs than the anti- PD-L1 drugs. 51 Up-to-date examples listed in this class are the anti-PD1 nivolumab, pembrolizumab, pidilizumab, and AMP-224.…”
Section: Action Mechanisms: Dissimilarities Among Anti- Pd1 and Anti-mentioning
confidence: 99%
See 1 more Smart Citation
“…Immune checkpoint inhibitors (ICIs) that can block immunosuppressive molecules such as programmed cell death‐protein 1 (PD‐1) or its ligand PD‐L1, and cytotoxic T‐lymphocyte associated protein 4 have been proven to be effective in treating various kinds of cancers by restoring antitumor immunity. ICIs that have been clinically applied to NSCLC include pembrolizumab, nivolumab, atezolizumab, durvalumab, and ipilimumab . Several prospective studies have demonstrated that both ICIs monotherapy and combination regimens showed encouraging efficacies in the treatment of NSCLC .…”
Section: Introductionmentioning
confidence: 99%
“…ICIs that have been clinically applied to NSCLC include pembrolizumab, nivolumab, atezolizumab, durvalumab, and ipilimumab. [5][6][7][8][9][10] Several prospective studies have demonstrated that both ICIs monotherapy and combination regimens showed encouraging efficacies in the treatment of NSCLC. 11,12 An early meta-analysis conducted by Wang et al provided clinical evidence that either ICI monotherapy or in combination with chemotherapy improved survival in patients with advanced NSCLC, and ICI group had fewer adverse events (AEs).…”
Section: Introductionmentioning
confidence: 99%